Decreased complement 4 and interleukin-10 as biomarkers in aqueous humour for non-exudative age-related macular degeneration: a case control study - Juliane Schikora; Aaron Dort; Hannah N. Wolf; Mihály Józsi; Richard B. Pouw; Thomas Bertelmann; Dirk Bahlmann; Christian van Oterendorp; Nicolas Feltgen; Hans Hoerauf; Diana Pauly; Jannis Klemming (Journal of Translational Medicine)
Abstract Background The development of age-related macular degeneration (AMD) is influenced by risk factors that contribute to inflammatory processes, cellular stress responses, and a dysregulation of the complement system. Given the incomplete understanding of the pathogenesis of AMD and the necessity for novel therapeutics, biomarker studies investigating aqueous humour from the anterior chamber of the eye serve as a valuable tool. This pilot study aimed to assess inflammatory mediators and complement components in aqueous humour of non-exudative AMD patients in comparison with a control group. Methods The aqueous humour of 12 non-exudative AMD patients and 21 control subjects was collected during cataract surgery. Levels of 78 inflammatory proteins and complement components were measured using multiplex immunoassays. The influence of sex or smoking on the AMD status was assessed using Pearson’s chi-square test. Biomarker levels between AMD patients vs. controls, smokers vs. non-smokers, and females vs. males were compared. Parametric datasets were analysed using independent-means t-test, while non-parametric data analysis was conducted utilising Wilcoxon’s rank-sum test. Spearman’s correlation investigated associations between drusen volume and biomarker levels, as well as biomarker levels and subject age. Results All examined 78 immunological factors were detectable in aqueous humour. The proteins were categorised into high, medium, and low level groups. Aqueous humour contained high levels of complement proteins, including iC3b, FH/FHL-1, C4B, and FI. Non-exudative AMD patients exhibited decreased levels of C4 (P = 0.020), IL-10 (P = 0.033), and FI (P = 0.082). A positive correlation was observed between drusen volume and CCL4 levels (r S  = 0.78, P = 0.013). Furthermore, smokers demonstrated significantly increased levels of pro-inflammatory proteins (CCL7, IL-7; P = 0.027, P = 0.030). MMP-1 was positively correlated with age (r S  = 0.44, P = 0.010), while sex differences were observed in FB (P = 0.027) and C4B (P = 0.036) levels. Conclusions This pilot study presents an initial overview of inflammation-associated biomarkers in the aqueous humour, highlighting potential roles for C4 and IL-10 in the development of non-exudative AMD. A larger, more-focused follow-up study is in progress to further investigate biomarkers localised to the eye and refine our understanding of AMD.